Marriage equality in the United States: a look at Obergefell and beyond - Jaeger-Fine, Toni (Revista de Investigações Constitucionais, 2016)
The article aims to analyze the marriage equality in the United States, with a special focus at Obergefell v. Hodges case, in which the US Supreme Court held, in June 2015, in a 5-4 decision that is unconstitutional to forbid same-sex marriage. Furthermore, it analyzes the Supreme Court jurisprudence about some issues related to this discussion and the democratic movement in the states in favor of same-sex marriage in the years leading up to Obergefell. Lastly, it makes some modest observations about the case and the larger issue of gay marriage in the United States.